2010
DOI: 10.1088/0953-4075/43/12/125204
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of the 200 nm diffuse band in zinc vapour and its interpretation

Abstract: The absorption spectrum of zinc vapour is measured under various conditions in the 190-224 nm region and the absolute absorption coefficient per pair of atoms is derived. A relatively narrow diffuse band at 200.22 nm (in a vacuum) is observed and its profile is carefully determined for several temperatures. It is found that the band maximum slightly decreases with a temperature increase. This indicates that the band is generated by transitions occurring within the range of negative energy values of the ground-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In our recent papers [19,20], we have demonstrated that it is possible to eliminate the hot S-R bands when the oven used for heating the absorption cell is flushed by any inert gas. Under such conditions, the present studies for the Zn and Cd dimers were undertaken, aimed at deriving more adequate characteristics of the interaction potentials at long distances, particularly concerning dispersion contributions to their energy, for the first singlet excited states of these species.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent papers [19,20], we have demonstrated that it is possible to eliminate the hot S-R bands when the oven used for heating the absorption cell is flushed by any inert gas. Under such conditions, the present studies for the Zn and Cd dimers were undertaken, aimed at deriving more adequate characteristics of the interaction potentials at long distances, particularly concerning dispersion contributions to their energy, for the first singlet excited states of these species.…”
Section: Introductionmentioning
confidence: 99%